Pemberian Ekstrak Curcuma Longa L. Meningkatkan Proliferasi Sel MEF yang dilakukan Scratch Test - Afiat Berbudi; Muhammad Ifham Hanif; Almahitta Cintami Putri (Poltekkes Kemenkes Pontianak, 2019)
Abstract: Proliferation Enhancement of Curcuma Longa L. Extract Treatment in MEF Cell Cultres that Treated by Scratch Test. Wound prevalence is still high and becomes a problem of healing process. Improper wounds management can cause wound healing disturbance, so that the healing process will be longer. For this reason, alternative medicine is required to shorten healing process and reduce medical costs. This study aims to determine the eï¬€ect of Curcuma longa L. extract on enhancement of mouse embryonic fibroblast cell proliferation carried out in vitro scratch test with the research method using a laboratory in vitro experimental design and 24 hour observation. Observations were carried out for 24 hours with variations in Curcuma longa L. extract concentration 2.5 ppm, 5 ppm, 10 ppm, 25 ppm and 50 ppm. The results showed that Curcuma longa L extract was able to accelerate the proliferation of mouse embryonic fbroblast cells which scratch test. After 24 hours, the highest gap closure were observed in mouse embryonic fbroblast cell culture using dose of 2.5 ppm of Curcuma longa L. extract administration. At a dose of â‰¥10 ppm it does not show proliferation in embryonic fbroblast mouse cells but causes toxicity to cells.Â Abstrak: Pemberian Ekstrak Curcuma Longa L. Meningkatkan Proliferasi Sel MEF yang dilakukan Scratch Test. Prevalensi luka yang tinggi masih menjadi permasalahan tersendiri dalam proses penyembuhan. Penanganan luka yang tidak tepat dapat menyebabkan gangguan penyembuhan sehingga proses penyembuhan menjadi panjang. Untuk itu perlu alternatif pengobatan yang dapat mempersingkat penyembuhan dengan biaya pengobatan yang lebih murah. Penetian ini bertujuan mengetahui pengaruh pemberian ekstrak Curcuma longa L. terhadap peningkatan proliferasi sel mouse embryonic fibroblast yang dilakukan scratch test secara in vitro dengan metode penelitian menggunakan desain eksperimen in vitro laboratoris dan dilakukan pengamatan selama 24 jam. Variasi konsentrasi ekstrak Curcuma longa L menggunakan dosis 2.5 ppm, 5 ppm, 10 ppm, 25 ppm dan 50 ppm. Hasil pengamatan menunjukkan bahwa ekstrak Curcuma longa L. mampu mempercepat proliferasi sel mouse embryonic fbroblast yang dilakukan scratch test dengan dosis optimum 2.5 ppm. Pada dosis â‰¥10 ppm tidak menunjukkan proliferasi pada sel mouse embryonic fbroblast tetapi menyebabkan toksisitas pada sel.